Ancient carved ambers in the J. Paul Getty Museum - Causey, Faya (Getty Publications virtual library., 2019)
"This catalogue provides a general introduction to amber in the ancient world followed by detailed catalogue entries for fifty-six Etruscan, Greek, and Italic carved ambers from the J. Paul Getty Museum. The volume concludes with technical notes about scientific investigations of these objects and Baltic amber"--Provided by publisher.